Pembinaan Ekstrakurikuler Olahraga SDN Lempongsari Kecamatan Gajah Mungkur Kota Semarang (Indonesian Journal for Physical Education and Sport, 2020)
One of the extracurricular problems in schools today is that the achievements achieved are not optimal, including at SD Lempongsari. The purpose of this study was to determine extracurricular coaching, extracurricular programs, and extracurricular student achievement in SD N Lempongsari. Qualitative descriptive research was conducted at SD N Lempongsari through coaching. This type of descriptive qualitative research uses a case study design that is extracting data and information about extracurricular guidance of SD N Lempongsari and interviews, observations, documentation while in the field. From the results of the study, SD N Lempongsari addressed in Gajah Mungkur District, Semarang City, Central Java. Recruitment is done when training takes place at school, the training program is held a month before the championship and is tiered from grade 3 to grade 5, SD N Lempongsari achievements in 2018 POPDA takraw wins 3 rd, 2019 wins 1 st. Conclusions, the data generated after the interview of the source of all data has been going well and the trainer training program is in accordance with their duties and authority. Suggestions, this research was not made to make SD N Lempongsari worse, but this research would be a preliminary data from poorer schools to better. It would be better if the Principal of SD N Lemponsari continued to pay attention to sports extracurricular coaching and student achievement for schools continued to survive and improve each year